Research Directions in Genetic Predispositions to Stevens–Johnson Syndrome / Toxic Epidermal Necrolysis. Issue 3 (6th November 2017) - Manolio, Teri A.; Hutter, Carolyn M.; Avigan, Mark; Cibotti, Ricardo; Davis, Robert L.; Denny, Joshua C.; Grenade, Lois La; Wheatley, Lisa M.; Carrington, Mary N.; Chantratita, Wasun; Chung, Wen‐Hung; Dalton, Andrea D.; et al.
Abstract : Stevens–Johnson syndrome/toxic epidermal necrolysis (SJS/TEN) is one of the most devastating of adverse drug reactions (ADRs) and was, until recently, essentially unpredictable. With the discovery of several risk alleles for drug‐induced SJS/TEN and the demonstration of effectiveness of screening in reducing incidence, the stage is set for implementation of preventive strategies in populations at risk. Yet much remains to be learned about this potentially fatal complication of commonly used drugs.